2021
DOI: 10.1002/rcm.9169
|View full text |Cite
|
Sign up to set email alerts
|

A boronic acid–modified C60 derivatization reagent for the rapid detection of 3‐monochloropropane‐1,2‐diol using matrix‐assisted laser desorption/ionization‐mass spectrometry

Abstract: Rationale: 3-Monochloropropane-1,2-diol (3-MCPD) is a well-known contaminant formed in food thermal processing, which could be found in a variety of foodstuffs.Due to its potential carcinogenicity, it was essential to quickly develop a rapid and high-throughput analytical method to monitor 3-MCPD in foodstuffs, which is described in this study.Methods: 3-MCPD was extracted from foodstuffs and then was derivatized with a boronic acid-modified C 60 (B-C 60 ) through the boronic acid-diol reaction. Microwave heat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Unfortunately, 3-MCPD is rather difficult to detect by MS and particularly MALDI-MS. This study [ 60 ] has shown that derivatization of 3-MCPD with a boronic acid-modified C60 (B-C60) through the boronic acid-diol reaction facilitates the detection of 3-MCPD significantly. A detection limit of 9 ng could be achieved under these experimental conditions.…”
Section: Which Matrix Is Most Suitable For Individual Lipid Classes?mentioning
confidence: 99%
“…Unfortunately, 3-MCPD is rather difficult to detect by MS and particularly MALDI-MS. This study [ 60 ] has shown that derivatization of 3-MCPD with a boronic acid-modified C60 (B-C60) through the boronic acid-diol reaction facilitates the detection of 3-MCPD significantly. A detection limit of 9 ng could be achieved under these experimental conditions.…”
Section: Which Matrix Is Most Suitable For Individual Lipid Classes?mentioning
confidence: 99%